A bridge scour risk management approach to deal with uncertain climate future. (January 2023) - Sasidharan, Manu; Kumar Parlikad, Ajith; Schooling, Jennifer; Hadjidemetriou, Georgios M.; Hamer, Matthew; Kirwan, Andy; Roffe, Steve
Highlights: A framework for bridge scour risk management in an uncertain climate future. A systematic approach to estimating scour risk ratings in different climate scenarios. Local scour progression is fastest during the initial 48 h of a peak flow event. Accelerated scour risk progression even in low emission climate scenario (RCP2.6). Abstract: Riverine bridges are under a substantial threat of scour due to the magnitude and frequency of floods arising due to climate change. Infrequent inspections, inadequate data on foundation depths, and the lack of consideration of hydrologic and climate parameters often result in uncertainties within current scour risk assessments. This paper presents an approach for assessing the risk progression of local scour in peak flow conditions that consider uncertainties associated with location, downscaling of climate predictions, and hydrologic, hydraulic and scour prediction models. A rational scour risk rating based on warning time to failure is introduced that can provide a useful addition to the existing bridge condition indexes. The case study on a set of railway bridges in Southeast England shows that climate change could accelerate the scour risk progression, even in the low-emission scenario. The approach and results form a vital basis for scour risk mitigation and climate adaptation planning.